Pola Interaksi Bakteri Endofitik +GFP (Green Fluorescent Protein) dalam Jaringan Tanaman Padi (oryza sativa l.) - Sufianto Sufianto (Jurnal Nasional Teknologi Terapan (JNTT), 2018)
This study was intended to examine the pattern of interaction and mutant distribution of endophyticbacteria as a result of the transformation of the gfp gene in rice plant tissue in vitro. This study used 5isolates of rice endophytic gfp mutants namely IM-1, IM-3, IM-8, IM-24, IM-25. The study wasconducted in two stages, stage I using a simple Complete Complete Design (RAL) and stage II usingfactorial Complete Randomized Design (RAL) with a factor of 1: the type of plant tissue and factor 2:the type of mutant isolates.The results of the study of patterns of bacterial interactions in rice tissueculture showed that the percentage of infections of 5 gfp mutant endophytic bacteria isolates rangedfrom 4% -17%. The highest percentage was in mutant isolates IM-3 + gfp (17%) and the lowest was inmutants IM-8 + gfp (4%). The interaction pattern was not significantly different from the parametersof seed germination time. On the other hand, in observing the distribution of bacteria that infect ricetissue, they showed different pattern. Mutant IM-1 + gfp infection is higher in stem tissue, whereasIM-24 + gfp mutant infection is higher in root tissue and IM-25 + gfp mutant infection is higher inleaf tissue. Mutant infection of IM-25 + gfp in leaves had the highest number of colonies reaching1.64 x 109 cfu/ml.